2013
DOI: 10.1161/strokeaha.113.002859
|View full text |Cite
|
Sign up to set email alerts
|

Severe Renal Impairment Is Associated With Symptomatic Intracerebral Hemorrhage After Thrombolysis for Ischemic Stroke

Abstract: All patients with stroke who received iv-tPA within 4.5 hours of symptom onset at our institution between January 2005 and August 2012 were included. Iv-tPA was administered according to European license. The register has been described in detail elsewhere.7 Serum creatinine levels (mmol/L) were measured for each patient on admission. Renal function was assessed by estimated GFR using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formula.8 Patients on dialysis were excluded. GFR values were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 14 publications
1
19
1
Order By: Relevance
“…We compared our results with those of the previous 6 related studies (table 4) [8,9,10,11,21,22]. Notably in the largest previous study [22], severe renal impairment (eGFR <30 ml/min/1.73 m 2 ) was independently associated with SICH (odds ratio, OR: 3.75; 95% confidence interval, CI: 1.44-9.80). In another large Japanese cohort, renal dysfunction was an independent risk factor for SICH, poor outcome and mortality at 3 months [11].…”
Section: Discussionmentioning
confidence: 87%
“…We compared our results with those of the previous 6 related studies (table 4) [8,9,10,11,21,22]. Notably in the largest previous study [22], severe renal impairment (eGFR <30 ml/min/1.73 m 2 ) was independently associated with SICH (odds ratio, OR: 3.75; 95% confidence interval, CI: 1.44-9.80). In another large Japanese cohort, renal dysfunction was an independent risk factor for SICH, poor outcome and mortality at 3 months [11].…”
Section: Discussionmentioning
confidence: 87%
“…An explanation of this result remains speculative, but we suppose that the monocenter approach and the sample size of our investigation may contribute to this finding. Data on whether RD represents an independent risk factor for ICH after rtPA treatment are highly incongruent, as some studies found a significant association while others did not [3,5,6,7,8,9,30,31]. However, there is some evidence that microbleeds are associated with an elevated risk of ICH after rtPA treatment [32] and this brain pathology is particularly common in patients with RD [33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore GFR < 30 mL/min was strongly associated with a poor outcome. In several studies increased risk of hemorrhagic complications was observed after received thrombolytic therapy in patients with renal dysfunction [10,12,16,20]. However Power A. et al did not found any significant association between renal impairment and higher rate of sICH (symptomatic intracerebral hemorrhage).…”
Section: Discussionmentioning
confidence: 97%
“…In this study GFR level lower than 61.65 mL/min/1.73m 2 before treatment was determined as a poor prognostic biomarker especially in patients with severe stroke (NIHSS > 14). Previous reports on the relationship between renal dysfunction and the risk of a poor outcome were conflicting [10][11][12][13][14][15][16][17][18][19][20]. Among these studies, a GFR level lower than 60 mL/min mostly was used as the definition of renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%